1994
DOI: 10.1002/anie.199411631
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Selective Coloration of Cryptand‐Type Crown Spirobenzopyrans for Alkaline‐Earth Metal Cations

Abstract: One equivalent of Ca2+ and Sr2+ ions induces the isomerization of the colorless spirobenzopyrans 1a (n = 1) and 1b (n = 2), respectively, to the colored merocyanines 2. Compounds of type 1 thus function as ion‐selective chemical sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…84 The crown ring cavity was varied in size. The addition of alkaline earth metal cation to acetonitrile solutions of compounds 65, 66, and 67 resulted in the appearance of broad absorption bands in the visible region with maxima depending on the metal coordinated by the cryptand.…”
Section: Photoswitchable Receptors Based On Spiropyransmentioning
confidence: 99%
“…84 The crown ring cavity was varied in size. The addition of alkaline earth metal cation to acetonitrile solutions of compounds 65, 66, and 67 resulted in the appearance of broad absorption bands in the visible region with maxima depending on the metal coordinated by the cryptand.…”
Section: Photoswitchable Receptors Based On Spiropyransmentioning
confidence: 99%
“…14,[22][23][24] Recognition of transition metal ions has been largely developed. By absorption and 1 H NMR analysis, they found that the molecules could selectively uptake and release alkali and alkaline-earth metal ions by manipulation of light, thus acting as photoswitchable sensors.…”
Section: Photochromic Sensors For Metal Ionsmentioning
confidence: 99%
“…Moreover, the relative strong chelating capability of N, O-atoms of the merocyanine with all heavy and transition metal ions makes it rather difficult to discriminate between chemically closely related cations [21]. In order for a spiropyran to selectively respond to a metal ion, more sophisticated systems, with multiple metal binding sites in the spiropyran-crown (or cryptand) ether conjugates have been developed [25][26][27][28]. However, the synthesis of such spiropyrans that comprise an appended crown accepts is a trivial task.…”
Section: Introductionmentioning
confidence: 99%
“…Using the unique properties of molecule binding and photochromism, spiropyrans have been employed not only in material chemistry for optical data store [19], but also in analytical chemistry as molecular sensors for metal ions (Scheme 1A) [20]. During the past decades, a number of diverse spiropyrans have been synthesized for optical sensing of heavy and transition metal ions [21][22][23][24], alkali metal [25,26] and alkaline-earth metal ions [27,28], and lanthanide ions [29,30].…”
Section: Introductionmentioning
confidence: 99%